An introduction to the literature of Equatorial Guinea between colonialism and dictatorship - Lewis, Marvin A., 1942- (Afro-romance writers., 2007)
"Examines how postcolonial literature depicts the clash of traditional and European cultures, reflects the impact of the Macías reafricanization process, and addresses the themes of individual and national identity, Hispanic heritage, and the Equatoguinean diaspora"--Provided by publisher.